2006
DOI: 10.1139/o06-176
|View full text |Cite
|
Sign up to set email alerts
|

PRAF1: a Golgi complex transmembrane protein that interacts with virusesThis paper is one of a selection of papers published in this Special Issue, entitled CSBMCB — Membrane Proteins in Health and Disease.

Abstract: Prenylated Rab acceptor domain family member 1 (PRAF1), a transmembrane protein whose precise function is unknown, localizes to the Golgi complex, post-Golgi vesicles, lipid rafts, endosomes, and the plasma membrane. VAMP2 and Rab3A are SNARE proteins that interact with PRAF1, and, as part of a SNARE complex, PRAF1 may function in the regulation of docking and fusion of transport vesicles both in the Golgi complex and at the plasma membrane. Alternately, PRAF1 may function as a sorting protein in the Golgi com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Sivars and colleagues [43] proposed a third function of PRA1 as a guanine nucleotide dissociation inhibitor (GDI) displacement factor (GDF) that aids in recycling Rabs during vesicular trafficking. An additional role for PRA1 in lipid transport, modulation of lipid homeostasis, and cell migration has been proposed based on proteomic analysis of PRA1 depleted nasopharyngeal carcinoma cells [44] and further supported by studies implicating PRA1 in the fusion of transport vesicles with the plasma membrane [45]. Finally, evidence supports a role for PRA1 in transport and assembly of viral proteins, although in some cases it may play an inhibitory role [45-49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sivars and colleagues [43] proposed a third function of PRA1 as a guanine nucleotide dissociation inhibitor (GDI) displacement factor (GDF) that aids in recycling Rabs during vesicular trafficking. An additional role for PRA1 in lipid transport, modulation of lipid homeostasis, and cell migration has been proposed based on proteomic analysis of PRA1 depleted nasopharyngeal carcinoma cells [44] and further supported by studies implicating PRA1 in the fusion of transport vesicles with the plasma membrane [45]. Finally, evidence supports a role for PRA1 in transport and assembly of viral proteins, although in some cases it may play an inhibitory role [45-49].…”
Section: Discussionmentioning
confidence: 99%
“…An additional role for PRA1 in lipid transport, modulation of lipid homeostasis, and cell migration has been proposed based on proteomic analysis of PRA1 depleted nasopharyngeal carcinoma cells [44] and further supported by studies implicating PRA1 in the fusion of transport vesicles with the plasma membrane [45]. Finally, evidence supports a role for PRA1 in transport and assembly of viral proteins, although in some cases it may play an inhibitory role [45-49]. These proposed functions for PRA1 are in no way mutually exclusive and in many cases are overlapping.…”
Section: Discussionmentioning
confidence: 99%
“…RABAC is involved in the assembling of retro and rotavirus and in the inhibition of the herpes life cycle [62]. The under expression of this gene in infected compared to control spat suggests a failure to slow the progression of the lytic phases of the herpes virus cycle.…”
Section: Discussionmentioning
confidence: 99%
“…293 Nonetheless, studies have also shown an interaction of PRA1 with proteins from other viruses, including a lipid raft-associated rotavirus spike protein (VP4) 294,295 and the LMP1 oncoprotein of Epstein-Barr virus 296 (reviewed in Ref. 297 ).…”
Section: General Models For Hiv-1 Env Glycoprotein Incorporationmentioning
confidence: 99%